Epigenetic Therapies for Heart Failure: Current Insights and Future Potential - Napoli, Claudio (Vasc Health Risk Manag, 2021)
Despite the current reductionist approach providing an optimal indication for diagnosis and treatment of patients with heart failure with reduced ejection fraction (HFrEF), there are no standard pharmacological therapies for heart failure with preserved ejection fraction (HFpEF). Although in its infancy in cardiovascular diseases, the epigenetic-based therapy (“epidrugs”) is capturing the interest of physician community. In fact, an increasing number of controlled clinical trials is evaluating the putative beneficial effects of: 1) direct epigenetic-oriented drugs, eg, apabetalone, and 2) repurposed drugs with a possible indirect epigenetic interference, eg, metformin, statins, sodium glucose transporter inhibitors 2 (SGLT2i), and omega 3 polyunsaturated fatty acids (PUFAs) in both HFrEF and HFpEF, separately. Apabetalone is the first and unique direct epidrug tested in cardiovascular patients to date, and the BETonMACE trial has reported a reduction in first HF hospitalization (any EF value) and cardiovascular death in patients with type 2 diabetes and recent acute coronary syndrome, suggesting a possible role in secondary prevention. Patients with HFpEF seem to benefit from supplementation to the standard therapy with statins, metformin, and SGLT2i owing to their ability in reducing mortality. In contrast, the vasodilator hydralazine, with or without isosorbide dinitrate, did not provide beneficial effects. In HFrEF, metformin and SGLT2i could reduce the risk of incident HF and mortality in affected patients whereas clinical trials based on statins provided mixed results. Furthermore, PUFAs diet supplementation was significantly associated with reduced cardiovascular risk in both HFpEF and HFrEF. Future large trials will reveal whether direct and indirect epitherapy will remain a work in progress or become a useful way to customize the therapy in the real-world management of HFpEF and HFrEF. Our goal is to discuss the recent advancement in the epitherapy as a possible way to improve personalized therapy of HF.